Lore Lindu National Park Forest Fire Control Strategy - Asa, Syukur; Malik, Adam; Dg. Massiri, Sudirman (Mitra Sains, 2022)
Forest fire is one of disturbances of the Lore Lindu National Park (LLNP) area caused by the people who live around LLNP. The purposes of this study were to develop a fire control strategy in LLNP area. The research was conducted through survey and interview activities which were completed with a list of questions (questionnaires). Respondents were selected by purposive sampling. Moreover, data analysis used descriptive analysis and SWOT analysis. The results showed that the types is surface forest fires with socio-cultural caused by the community around the LLNP area. Furthemore, the strategy for control forest fire is by empowering local communities in controling forest fires in LLNP.